ASSORTMENT POLICY IMPROVEMENT OF THE MEGOGO COMPANY - С. О. Солнцев; А. Є. Салата (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
This article is devoted to the improvement of theoretical and methodological provisions and the development of practical recommendations for managing the assortment policy of IPTV services in conditions of market uncertainty to increase efficiency. The author's definition of assortment policy is submitted. The main structural elements of the assortment policy are characterized: by product management, assortment management, and product item elimination. The assortment policy management algorithm is presented. The main properties of the assortment are summarized and the characteristics of their measurements are given. A model of situational analysis and enterprise management in conditions of uncertainty has been developed. The article proposes the improvement of the assortment policy in the digital television market. A brief overview of the IPTV and OTT markets is provided. It has been established that Megogo is the leader of IPTV television and direct OTT services in Ukraine. An analysis of the company's assortment and value chain was carried out. The main areas of improvement of the assortment policy of Megogo have been identified. The company's situational management algorithm has been developed. The effectiveness of the proposed measures to improve the assortment policy for the Megogo company was evaluated.